AKUNTABILITAS FINANSIAL DALAM PENGELOLAAN ALOKASI DANA DESA (ADD) (Studi Kasus di Desa Sumbersuko Kecamatan Purwosari Kabupaten Pasuruan) - Nur Syuroidah; Noor Shodiq Askandar; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThe original fund of the village is the income earned and extracted from theincome potential of the village. Regional revenue groups consist of: business results,asset yields, self-reliance, participation, and mutual assistance, and other village originalrevenues. While the transfer earnings represent village revenues earned from otherentities such as transfers from municipal and district governments, transfers fromprovincial governments, and transfers from the central government. The realization offunding from APBD that is channeled through the Village Fund Allocation (ADD) shouldreally make the village prosperity. However, in the implementation and accountabilitysometimes there are still some obstacles that often faced in its management because it isnot in accordance with the principle of regional financial management in accordancewith Regulation of Minister of Home Affairs No. 113 of 2014 that in every managementmust be based on the principle of transparency and accountability. Based on thesematters it encourages the authors to conduct research related to accountability andmanagement of Village Fund Allocation. This research is a qualitative descriptive study.The collection was conducted interview, observation, and documentation. The results ofthis research is the Planning Stage of Village Fund Allocation (ADD) in SumbersukoVillage Already in accordance with Regulation of Pasuruan Regent No.13 of 2015.Keywords: Accountability, Governance administration, Governance fund allocation(ADD)